Alcohol Inhibits Odontogenic Differentiation of Human Dental Pulp Cells by Activating mTOR Signaling - Wei Qin; Qi-Ting Huang; Michael D. Weir; Zhi Song; Ashraf F. Fouad; Zheng-Mei Lin; Liang Zhao; Hockin H. K. Xu (Stem Cells International)
Long-term heavy alcohol consumption could result in a range of health, social, and behavioral problems. People who abuse alcohol are at high risks of seriously having osteopenia, periodontal disease, and compromised oral health. However, the role of ethanol (EtOH) in the biological functions of human dental pulp cells (DPCs) is unknown. Whether EtOH affects the odontoblastic differentiation of DPCs through the mechanistic target of rapamycin (mTOR) remains unexplored. The objective of this study was to investigate the effects of EtOH on DPC differentiation and mineralization. DPCs were isolated and purified from human dental pulps. The proliferation and odontoblastic differentiation of DPCs treated with EtOH were subsequently investigated. Different doses of EtOH were shown to be cytocompatible with DPCs. EtOH significantly activated the mTOR pathway in a dose-dependent manner. In addition, EtOH downregulated the alkaline phosphatase activity, attenuated the mineralized nodule formation, and suppressed the expression of odontoblastic markers including ALP, DSPP, DMP-1, Runx2, and OCN. Moreover, the pretreatment with rapamycin, a specific mTOR inhibitor, markedly reversed the EtOH-induced odontoblastic differentiation and cell mineralization. Our findings show for the first time that EtOH can suppress DPC differentiation and mineralization in a mTOR-dependent manner, indicating that EtOH may be involved in negatively regulating the dental pulp repair.